THE MYSTIFICATION OF ADORNO’S “ENLIGHTENMENT” IN MUSIC INDUSTRIES - BĂLAN, Oana (Studia Universitatis Babes-Bolyai Musica, 2016)
Forty years ago we were at the beginning of a time when “music industries” were becoming the object of academic and political preoccupation. A fundamental piece of work for the field of philosophy, written by Theodor Adorno and Max Horkheimer, presents the intransigent analysis of ideological cultural trends produced during the Enlightenment and used to educate and control the “mass” social layer. The study is important for the history of cultural management due to the identification of the first acknowledgements of the cultural consumption markets and the commercial connotation associated to music by an aesthetic category named “artistic commodity value”. Although the debate seems pejorative, if we relate it to the contemporary theories and to the applicability that this field enjoys nowadays, it will remain in the exegetes’ conscience as a moment of historical reference. Adorno is the one who introduced the term cultural “industry” into the practice of management.